AB0525 Clinical and renal histologial characteristics of patients with systemic lupus erythematosus with anti-ss-a and anti-ss-b antibodies compared to those without. (15th June 2017) - Anan, R; Kaneko, Y; Kikuchi, J; Ushikubo, M; Saito, S; Takeuchi, T
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic condition with a broad clinical spectrum, which can affect multiple organs and systems. Although the most featuristic autoantibodies are anti-DNA and anti-Sm antibodies, anti-SS-A antibody and anti-SS-B antibody are detected in 30–40% and 7–45% of SLE patients, respectively. However, the clinical features of those positive patients are unclear. Objectives: The aim of this study was to clarify the associations of anti-SS-A and anti-SS-B antibodies with the clinical features of SLE and histological findings of lupus nephritis (LN). Methods: We enrolled consecutive Japanese patients with SLE who had visited Keio University Hospital from 2013 to 2015 and whose anti-SSA and anti-SSB antibodies were measured. The patients were divided according to the presence or absence of anti-SS-A and anti-SS-B antibodies, and their associations of the clinical features and renal biopsy histological findings were examined. Results: A total of 253 patients were enrolled, 215 (84%) were female, and the mean age was 55.2 years. Anti-SS-A antibody was detected in 152 cases (69%), and anti-SS-B antibody in 40 cases (18%). No difference was found in sex, age, the rates of anti-DNA and anti-Sm positivity between both the anti-SS-A positive group and the anti-SS-A negative group, and between the anti-SS-B positive group and the anti-SS-B negative group. While the frequencies of oral ulcers (38% vs. 37%, p=0.83), arthritis (82% vs. 79%, p=0.58), serositis (23% vs. 22%, p=0.94), neuropsychiatric involvement (14% vs. 10%, p=0.35), LN (51% vs. 63%, p=0.07), leukopenia (74% vs. 69%, p=0.44), and thrombocytopenia (26% vs. 31%, p=0.44) were not different between the anti-SS-A positive group and the anti-SS-A negative group, .mucocutaneous involvement (84% vs. 63%, p=0.002), alopecia (37% vs. 19%, p=0.002), lymphopenia (97% vs. 89%, p=0.020) were significantly higher in the anti-SS-A positive group than the anti-SS-A negative group. The frequencies of neuropsychiatric involvement (24% vs. 10%, p=0.015) was significantly higher in the anti-SS-B positive group than the anti-SS-B negative group. The period from the SLE onset to the LN onset was significantly shorter in the anti-SS-A positive group than the anti-SS-A negative group (4.0 years vs. 9.0 years, p=0.005), and in the anti-SS-B positive group than the anti-SS-B negative group (0.4 years vs. 6.8 years, p=0.008). Focusing on the histological findings of LN patients, the anti-SS-A positive group had significantly lower rate of renal tubular atrophy (8.0% vs. 16%, p=0.042) and interstitial fibrosis (7.6% vs. 16%, p=0.031) than the anti-SS-A negative group. The anti-SS-B positive group had also significantly lower rate of renal tubular atrophy (3.3% vs. 13%, p=0.048) and interstitial fibrosis (2.1% vs. 13%, p=0.016). Finally, chronicity Index was significantly lower in the anti-SS-A positive group (2.37 vs. 4.14, p=0.002) and in the anti-SS-B positive group (1.17 vs. 3.33, p=0.008). Conclusions: SLE patients positive for anti-SS-A and anti-SS-B antibodies had characteristics with frequent mucocutaneous involvement, alopecia, neuropsychiatric involvement, and lymphopenia. They should be followed carefully for early onset of LN. Disclosure of Interest: None declared